Molecular Tactics of Biocontrol Fungi to Hack Plant Immunity for Successful Host Colonization—A Focus on Trichoderma Fungi - Yingfen Yang; Meiwei Zhao; Guotao Li; Ying Wang; Qingqing Shen; Jun Yang; Tahani A. Y. Asseri; Yanjun Wang; Min Guo; Waqar Ahmed (Microorganisms)
To play a role effectively, biocontrol fungi must fight against plant immune response and establish a symbiotic interaction with their host. After successfully colonizing the host plant, the biocontrol fungi may deliver beneficial effects related to plant health and resistance against phytopathogens. These fungi use a variety of tactics to bypass the host immune response, including the production of effector proteins, miRNA interference, manipulation of host defense mechanisms, and others. In this review article, we discussed these strategies of biocontrol fungi based on recent findings. These methods enable the fungi to escape the plant’s intrinsic immunity and finely adjust the plant’s defense signaling cascades. Additionally, we discussed the importance of the physical barrier in the form of host cell walls and elucidated how biocontrol fungi use a combination of mechanical and enzymatic tactics to overcome this obstacle. Given the evolving comprehensions from molecular biology, genomics, and ecology, this review article highlights the prospective for a holistic, interdisciplinary approach to improve our understanding of the biocontrol mechanism.